2006
DOI: 10.4049/jimmunol.177.3.1434
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptidyl Peptidase II Is the Major Peptidase Needed to Trim Long Antigenic Precursors, but Is Not Required for Most MHC Class I Antigen Presentation

Abstract: Recent reports concluded that tripeptidyl peptidase (TPPII) is essential for MHC class I Ag presentation and that the proteasome in vivo mainly releases peptides 16 residues or longer that require processing by TPPII. However, we find that eliminating TPPII from human cells using small interfering RNA did not decrease the overall supply of peptides to MHC class I molecules and reduced only modestly the presentation of SIINFEKL from OVA, while treatment with proteasome inhibitors reduced these processes dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
91
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 46 publications
12
91
1
Order By: Relevance
“…A broader role for TPPII in cross-presentation was suggested by the finding that TPPII mediates trimming of proteasomal products 15 aa or longer for further processing and MHC class I binding (25). However, whether TPPII is indispensable for the generation of most MHC class I epitopes was challenged by another group who found that inhibition of TPPII by siRNA does not reduce the presentation of MHC class I epitopes in the presence of functional proteasomes (26). Analysis of epitopes generated by APCs from TPPII Ϫ/Ϫ mice suggests that TPPII has a moderately destructive role for certain epitopes (27).…”
Section: Discussionmentioning
confidence: 99%
“…A broader role for TPPII in cross-presentation was suggested by the finding that TPPII mediates trimming of proteasomal products 15 aa or longer for further processing and MHC class I binding (25). However, whether TPPII is indispensable for the generation of most MHC class I epitopes was challenged by another group who found that inhibition of TPPII by siRNA does not reduce the presentation of MHC class I epitopes in the presence of functional proteasomes (26). Analysis of epitopes generated by APCs from TPPII Ϫ/Ϫ mice suggests that TPPII has a moderately destructive role for certain epitopes (27).…”
Section: Discussionmentioning
confidence: 99%
“…That TPP2 is an essential protein is supported by the finding that homozygous knock down in mice and Caenorhabditis elegans is lethal (12). TPP2 is involved in antigen processing (13)(14)(15)(16)(17)(18), cell growth, DNA damage repair and carcinogenesis (19 -22), fat metabolism, feeding behavior, and obesity (12,23). While the majority of those processes has been linked to TPP2 by describing individual phenotype and expressional changes of TPP2 as well as connected individual proteins (24 -26), only antigen processing and feeding behavior have been directly related to TPP2 peptidase activity by identifying involved peptide substrates (6,9,10,23).…”
mentioning
confidence: 52%
“…While the majority of those processes has been linked to TPP2 by describing individual phenotype and expressional changes of TPP2 as well as connected individual proteins (24 -26), only antigen processing and feeding behavior have been directly related to TPP2 peptidase activity by identifying involved peptide substrates (6,9,10,23). TPP2 has been shown to generate a few specific epitopes via its endopeptidase activity, for instance, for specific HLA allele mediated peptide presentation (10,11,17,27). It has been suggested a role of TPP2 in obesity relies on exopeptidase cleavage of the satiety signaling neuropeptide cholecystokinin-8, which subsequently regulates feeding behavior (12,17,28).…”
mentioning
confidence: 99%
“…Several proteases have been implicated in the processing of endogenously synthesized antigens independent of the classical proteasome pathway as follows: signal peptidase (43,44); furin (45,46); tripeptidyl peptidase II (47)(48)(49); lysosomal chloroquine-sensitive enzymes (50,51); and caspases (52,53). In this study, diverse proteolytic activities are required to generate the two HLA-B7-restricted epitopes studied.…”
Section: Discussionmentioning
confidence: 96%